Phytochemical Diversity, Pharmacological Potential, and Nutraceutical Applications of Nigella sativa and Solanum melongena Seeds: An Integrative Review - Singh, Km. Diksha; Hemraj, Ramteke Kuldeep; Singh Rajput, Dharmendra; Gupta, Naveen (Journal of Neonatal Surgery, 2025)
Nigella sativa (Black Cumin) and Solanum melongena (Eggplant) seeds are emerging as versatile botanical resources with significant nutraceutical and functional food potential. This review comprehensively evaluates their phytochemical compositions, bioactivities, and current applications, integrating evidence from in-vitro, in-vivo, and limited clinical studies. Nigella sativa seeds are rich in thymoquinone, nigellone, and essential fatty acids, underpinning potent antioxidant, anti-inflammatory, antimicrobial, anticancer, and metabolic regulatory effects. Solanum melongena seeds, characterized by nasunin, chlorogenic acid, and phenolic acids, exhibit strong antioxidant and cardioprotective properties, along with favourable sensory attributes for food fortification. The nutraceutical applications of both seeds span dietary supplements, fortified bakery and dairy products, functional beverages, and polyphenol-rich extracts. Comparative analysis highlights complementary pharmacological profiles, suggesting synergistic benefits in combined formulations. Safety evaluations indicate low acute and subchronic toxicity at traditionally consumed dosages, while international regulatory recognition varies, with Nigella sativa enjoying broader acceptance. Despite promising evidence, gaps persist in clinical validation, standardization, and bioavailability optimization. Future research should prioritize large-scale randomized controlled trials, development of validated quality markers, and formulation innovations to enhance efficacy. Harnessing the complementary strengths of these seeds could yield next-generation nutraceuticals targeting oxidative stress, inflammation, cardiovascular health, and cognitive function. This review underscores the potential of Nigella sativa and Solanum melongena as integral components of evidence-based functional food and nutraceutical strategies.